The Crispr Revolution in Genome Engineering: Perspectives from Religious Ethics - Lee, Jung H. (Journal of religious ethics, 2022)
This focus issue considers the normative implications of the recent emergence in genome editing technology known as CRISPR (clustered regularly interspaced short palindromic repeats) or CRISPR-associated protein 9. Originally discovered in the adaptive immune systems of bacteria and archaea, CRISPR enables researchers to make efficient and site-specific modifications to the genomes of cells and organisms. More accessible, precise, and economic than previous gene editing technologies, CRISPR holds the promise of not only transforming the fields of genetics, agriculture, and human medicine, but also heralding a new era of democratized biotechnology. However, the speed with which developments in the field have progressed threatens to overwhelm our normative sensibilities about the long-term practical and ethical implications. The contributors to this focus issue attempt to think through some of the more salient moral and practical consequences of CRISPR in the context of religious ethics, particularly as they relate to themes of autonomy, human flourishing, social justice, and the ethics of enhancement.